PECULIARITIES OF A SEARCH OR INSPECTION OF HOUSING OR OTHER PROPERTY OF A PERSON UNDER THE CONDITIONS OF MARITIME STATE IN UKRAINE - Litvinova, Iryna; Lobay, Daria (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: to study the procedural features of the procedure for conducting a search or inspection of housing or other property of a person under martial law and to consider problematic issues of such investigative (search) actions in a special legal regime. Research methods: abstract-logical, comparative-legal, analytical and special-legal methods, in particular formal-legal and formal-logical methods. Results: changes in the legislation on pre-trial investigation in martial law have been made at the request of modern times and have a direct impact on the course of pre-trial investigation. These changes expand the powers of the prosecuting party, which is a matter of concern, as such investigative (investigative) actions in themselves restrict human rights, and in such circumstances can lead to significant violations of the rights of suspects and accused persons in criminal proceedings. Discussion: human rights and freedoms in Ukraine are the highest social value, martial law restricts these rights and freedoms, as well as the expanded powers of the prosecution in such circumstances as a result of changes, so a search or inspection of housing or other property should be carried out in compliance balance between the legality of actions, the least restriction of human rights and personal safety of persons involved in this investigative (investigative) action. Changes were introduced at the request of modernity, they have a direct impact on the course of criminal proceedings, and especially pre-trial investigation, under martial law. The caveat is that such changes expand the powers of the prosecution and may lead to a violation of the rights of the suspect and the accused in criminal proceedings. It is not for nothing that this draft law at the stage of its adoption was criticized by the legal community, however, the expediency and effectiveness of such changes can be confirmed or refuted exclusively by law enforcement practice.